Cytokine biomarkers for the diagnosis of tuberculosis infection and disease in adults in a low prevalence setting. (January 2019) - Clifford, Vanessa; Tebruegge, Marc; Zufferey, Christel; Germano, Susie; Forbes, Ben; Cosentino, Lucy; Matchett, Elizabeth; McBryde, Emma; Eisen, Damon; Robins-Browne, Roy; Street, Alan; Denholm, Justin; et al.
Abstract: Objective: Accurate and timely diagnosis of tuberculosis (TB) is essential to control the global pandemic. Currently available immunodiagnostic tests cannot discriminate between latent tuberculosis infection (LTBI) and active tuberculosis. This study aimed to determine whether candidate mycobacterial antigen-stimulated cytokine biomarkers can discriminate between TB-uninfected and TB-infected adults, and additionally between LTBI and active TB disease. Methods: 193 adults were recruited, and categorised into four unambiguous diagnostic groups: microbiologically-proven active TB, LTBI, sick controls (non-TB lower respiratory tract infections) and healthy controls. Whole blood assays were used to determine mycobacterial antigen (CFP-10, ESAT-6, PPD)-stimulated cytokine (IL-1ra, IL-2, IL-10, IL-13, TNF-α, IFN-γ, IP-10 and MIP-1β) responses, measured by Luminex multiplex immunoassay. Results: The background-corrected mycobacterial antigen-stimulated cytokine responses of all eight cytokines were significantly higher in TB-infected participants compared with TB-uninfected individuals, with IL-2 showing the best performance characteristics. In addition, mycobacterial antigen-stimulated responses with IL-1ra, IL-10 and TNF-α were higher in participants with active TB compared those with LTBI, reaching statistical significance with PPD stimulation, although there was a degree of overlap between the two groups. Conclusion: Mycobacterial antigen-stimulated cytokine responses may prove useful in future immunodiagnostic tests to discriminate between tuberculosis-infected and tuberculosis-uninfected individual, and potentially between LTBI and active tuberculosis.